2021
DOI: 10.3390/ijerph182312641
|View full text |Cite
|
Sign up to set email alerts
|

What about the Consequences of the Use of Distance Learning during the COVID-19 Pandemic? A Survey on the Psychological Effects in Both Children and Parents

Abstract: Background: The COVID-19 pandemic implicated many social restrictions, including the use of distance learning (DL). Indeed, parents were obligated to support their children in online lessons and schoolwork. The aim of this study was to investigate the psycho-emotional impact of the COVID-19 pandemic on parents and children submitted to DL. Methods: One hundred and ninety-two participants (96 parents and 96 children) were enrolled in this study. Parents and children completed an online questionnaire, structured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Although across six different national contexts, including Italy, the experience of the pandemic differed, associations between COVID-19-related family experiences and child adjustment difficulties were similar across countries in nature and magnitude [57]. In a small study performed in the province of Messina, Sicily, children aged 5-16 years reported higher levels of depressive symptoms and event-related anxiety, which increased as children got older, and stress and anxiety in parents were positively correlated with mood depression and anxiety in their children [58]. Similar observations were reported for another non-representative sample aged 7-18 years from different Italian regions [44].…”
Section: Discussionmentioning
confidence: 95%
“…Although across six different national contexts, including Italy, the experience of the pandemic differed, associations between COVID-19-related family experiences and child adjustment difficulties were similar across countries in nature and magnitude [57]. In a small study performed in the province of Messina, Sicily, children aged 5-16 years reported higher levels of depressive symptoms and event-related anxiety, which increased as children got older, and stress and anxiety in parents were positively correlated with mood depression and anxiety in their children [58]. Similar observations were reported for another non-representative sample aged 7-18 years from different Italian regions [44].…”
Section: Discussionmentioning
confidence: 95%
“…Although it has been vital in ensuring educational continuity during the pandemic, there is conflicting evidence about its impact on the mental well-being of both children and their parents. Several studies have revealed that remote learning during COVID-19 has increased stress, anxiety, and depression among students [ 32 , 40 ], also due to the prolonged use of technology [ 11 ]. However, the impact of remote learning on mental health varies based on individual circumstances, as emotional difficulties may be exacerbated by pre-existing mental health problems, social isolation, or familial conflicts [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the challenges of caregiving, mothers may also face additional challenges related to assisting with distance learning. With remote teaching, the child’s active involvement may be reduced, and parents may need to solve technical problems with the distance learning platforms, adding to the commitment of caregiving [ 40 ]. This may explain why these mothers did not benefit from distance learning in the same way as mothers of neurotypical children, for whom distance learning was a predictor of reduced stress.…”
Section: Discussionmentioning
confidence: 99%
“…However in a relevant number of cases distance learning has brought with it many psychological problems such as an increased level of restlessness, aggressiveness, anxiety, depression, irritability, boredom, inattention, a scarce commitment and autonomy during lessons in the youngest, and exacerbated the difficulty of children with pre-existing behavioral problems like autism and attention deficit hyperactivity disorder ( Maggio et al, 2021 ; Panda et al, 2021 ; Scarpellini et al, 2021 ), in some cases it has also stimulated the resilience of young people who have chosen to occupy an active role in the choice of methods, activities and organization, using the experience of distance education to develop more profound self-regulation and call for reshaped, more collaborative roles and relationships with teachers for the future ( Kovács Cerović et al, 2021 ). In particular, recent research has highlighted the importance of self-efficacy in developing and dealing with the experience of distance learning: adolescents most confident have emphasized their successes by making the best use of relational resources, whereas those less confident children have more strongly perceived the difficulties not only in learning but also in the more social aspects of the school ( Pelikan et al, 2021 ).…”
Section: Covid-19 At Schoolmentioning
confidence: 99%